2007
DOI: 10.1016/j.neuroimage.2006.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Neural activation to upright and inverted faces in infants measured by near infrared spectroscopy

Abstract: The present study examined infants' brain activity in response to upright and inverted faces using near infrared spectroscopy (NIRS), which can non-invasively record hemodynamic changes of the brain. NIRS is particularly useful for recording in infants, since recordings can be made, even while the infants are awake, without fixing their body and brain. For this objective, we used newly developed sensor probes of NIRS for recording in infants. We measured changes in cerebral oxygenation in 10 5-8-month-olds' le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
166
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(191 citation statements)
references
References 47 publications
(63 reference statements)
22
166
2
1
Order By: Relevance
“…Bhatt, et al, 2005;Otsuka et al, 2007;Turati, Sangrigoli, Ruely, & de Schonen, 2004) and adults (e.g. Yin, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Bhatt, et al, 2005;Otsuka et al, 2007;Turati, Sangrigoli, Ruely, & de Schonen, 2004) and adults (e.g. Yin, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…However, the oxy-haemoglobin and total-haemoglobin concentrations in 8-month-old infants increased for both frontal and profile views. These studies suggest that the right temporal hemisphere is specialised for face recognition in infants (Carlsson et al, 2008;Nakato et al, 2011;Nakato et al, 2009;Otsuka et al, 2007). Previous neuroimaging studies in adults also indicated that the right temporal cortex is involved in face recognition.…”
Section: Haemodynamic Responses In Infants During Face Recognitionmentioning
confidence: 93%
“…Haemodynamic changes during the face recognition process as assessed by NIRS have been documented in several studies (Blasi et al, 2007;Csibra et al, 2004;Grossmann et al, 2008;Honda et al, 2010;Ichikawa et al, 2010;Nakato et al, 2009Nakato et al, , 2011aNakato et al, , 2011bOtsuka et al, 2007). Newborns showed a spontaneous preference for face-like stimuli over non-face-like patterns (Fantz, 1961).…”
Section: Haemodynamic Responses In Infants During Face Recognitionmentioning
confidence: 95%
“…These monitors are used clinically in Japan in rehabilitation/orthopedic settings, in neonatal intensive care units (continuous brain blood flow measured over the fontanelle), and emergency medicine applications. They are approved for research in the U.S. and are used, for example, to assess sensory and motor performance (Bortfeld et al 2007;Hatakenaka et al 2007;Otsuka et al 2007). Sampling occurred every 10sec over a 5 min baseline period, then every 10sec during the 10 min PVT test and during recording of each P50 potential ISI.…”
Section: Near Infrared Spectroscopy (Nirs)mentioning
confidence: 99%